2014
DOI: 10.3892/or.2014.3286
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DJ-1 overexpression on the proliferation, apoptosis, invasion and migration of laryngeal squamous cell carcinoma SNU-46 cells through PI3K/AKT/mTOR

Abstract: Abstract. The aim of the present study was to explore the effect of DJ-1-mediated PI3K/AKT/mTOR pathway on the proliferation, apoptosis, invasion, migration and other tumor biological characteristics of laryngeal squamous cell SNU-46, through stable transfection and overexpression of the DJ-1 gene. Retrovirus carrying DJ-1 gene was used to stabilize transfected human laryngeal squamous carcinoma SNU-46 cell line, and monoclonal cell line of stably overexpressed DJ-1 protein was screened out by G418. DJ-1 prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…revealed that the overexpression of DJ-1 in laryngeal squamous carcinoma cells is correlated with increased expression of phosphorylated Akt (p-Akt) and the high intracellular levels of DJ-1 can accelerate proliferation rate, increase the invasiveness and migration capacity, and reduce apoptosis, by activating the PI3K/Akt/mTOR signaling axis. 52 It has been confirmed that the proliferation rate of DJ-1-overexpressing SNU-46-D1 cells was faster than normal SNU-46 cells. Through the modulation of this signaling axis DJ-1 has also been implicated in tumor growth and progression by upregulating hypoxia-inducible factor-1 (HIF1) protecting the cells against hypoxia induced apoptosis.…”
Section: Resultsmentioning
confidence: 86%
“…revealed that the overexpression of DJ-1 in laryngeal squamous carcinoma cells is correlated with increased expression of phosphorylated Akt (p-Akt) and the high intracellular levels of DJ-1 can accelerate proliferation rate, increase the invasiveness and migration capacity, and reduce apoptosis, by activating the PI3K/Akt/mTOR signaling axis. 52 It has been confirmed that the proliferation rate of DJ-1-overexpressing SNU-46-D1 cells was faster than normal SNU-46 cells. Through the modulation of this signaling axis DJ-1 has also been implicated in tumor growth and progression by upregulating hypoxia-inducible factor-1 (HIF1) protecting the cells against hypoxia induced apoptosis.…”
Section: Resultsmentioning
confidence: 86%
“…It is interesting to note that in addition to inhibition of mTOR pathway protein phosphorylation there was also increase in protein DJ-1 (gene PARK7 ) in the two relatively more AZD1208-sensitive cell lines, MOLM-16 and KG-1a. DJ-1 is involved with response to oxidative stress (reviewed in[27]) as well as promoting cancer cell invasion[2830]. DJ-1 activation may be a survival mechanism against blockade of Pim kinase and/or mTOR pathway signaling.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent apoptosis, DJ-1 and the Fas death domain-associated protein (Daxx) (gi|48146287) combine in the nucleus, thus preventing Daxx from associating with ASK1 (gi|5174547) and undergoing a translocation from the nucleus to the cytoplasm 36 . The DJ-1 protein negatively regulate the activity of PTEN (gi|4240387) 37 . Therefore, a lower expression of DJ-1 can decrease the phosphorylation of PKB/Akt, whereas a higher expression of DJ-1 can increase the PKB/Akt phosphorylation and cell survival 38 .…”
Section: Resultsmentioning
confidence: 99%